2013
DOI: 10.1002/anie.201302828
|View full text |Cite
|
Sign up to set email alerts
|

An Electron‐Precise, Tetrahedral μ3 Boride Complex

Abstract: Recent research into the transition-metal chemistry of boron has unveiled a remarkable ability of boron-based ligands to adopt a wide diversity of different coordination modes ( Figure 1). Classifications have been made by the number of substituents at boron and by the number of transition metals attached to the boron center. [1] Experimental and theoretical studies clearly identified a classical bonding situation with two-center-two-electron (2c2e) bonds for most borane (I) and boryl (II) complexes. By contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Previous TD-DFT calculations by our group on I Mesupported diaryldiborenes showed that, independento ft he natureo ft he aryl group, the highest wavelength absorption band alwaysc orresponds to the HOMO-LUMO transition, p(BÀB)!p(NHC), the 483-502nma bsorption band to the p(BÀB)!p(Aryl/NHC)t ransition and the lowest wavelength absorptionb and to the s(BÀB)!p(NHC) transition. [8,9] Based on these calculations,w epropose as imilara ssignment to the three absorption bands of each of the UV/Vis spectra presented in Figure 5, as outlined in Ta ble 4.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous TD-DFT calculations by our group on I Mesupported diaryldiborenes showed that, independento ft he natureo ft he aryl group, the highest wavelength absorption band alwaysc orresponds to the HOMO-LUMO transition, p(BÀB)!p(NHC), the 483-502nma bsorption band to the p(BÀB)!p(Aryl/NHC)t ransition and the lowest wavelength absorptionb and to the s(BÀB)!p(NHC) transition. [8,9] Based on these calculations,w epropose as imilara ssignment to the three absorption bands of each of the UV/Vis spectra presented in Figure 5, as outlined in Ta ble 4.…”
Section: Resultsmentioning
confidence: 98%
“…Unlike their solutions, which were deep purple (or pink in the case of [(I iPr )BTh Me2 ] 2 ), single crystalso f (13) 129.0(3) (C1,B1,B1',C10') [a] 0.0(3) 2.7(4) 0.7(5) 0.9 (7) 4.2(3) 3.7(2), 5.0(2) 0.1(5), 0.6(5) (B1',B1,C10,S1) [b] 0.9(2) 0.3(5) 20.6(3)6.4(4)51.2(3) 5.1(2), 22.7(2) 0.6(5), 1.8(5) (B1',B1,C1,N1) [c] 89.3(3)77.9(3) 76.5(3)83.0(5) 51.7(3) 72.9(2),6 5.1(2) 82.4(4), 79.3(4) (C14,N3,C13,S1) [d] -----73. 585(4)-1.593(5) ), [8] [9] indicating significant B=Bd ouble bond character.T he BÀC NHC bonds (1.582(2)-1.603(3) )a re considerably shortened compared to the borane precursors (1.613(3)-1.632(3 ), as expected when movingf rom sp 3 -t os p 2 -hybridized boron.E xcept in [(I iPr )BTh tms ] 2 ,t he NHC ligandsa re rotatedn ear orthogonally with respect to the central diborene plane (torsion angles: 70.6(2)-89.3(3)8)i no rder to minimize steric interactions with the thiophene substituents. The BÀC Th bonds, all around 1.56 in length, are 0.02-0.03 shorter than in the borane precursors, whichp oints to some degree of p-electron delocalization over the 1,2-dithienyldiborene framework.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations